Violence against Women with Chronic Maternal Disabilities in Rural Bangladesh - Naved, Ruchira T; Blum, Lauren S; Chowdhury, Sadia; Khan, Rasheda; Bilkis, Sayeda; Koblinsky, Marge (Journal of Health, Population and Nutrition, 2012)
This study explored violence against women with chronic maternal disabilities in rural Bangladesh. During November 2006July 2008, in-depth interviews were conducted with 17 rural Bangladeshi women suffering from uterine prolapse, stress incontinence, or fistula. Results of interviews showed that exposure to emotional abuse was almost universal, and most women were sexually abused. The common triggers for violence were the inability of the woman to perform household chores and to satisfy her husbands sexual demands. Misconceptions relating to the causes of these disabilities and the inability of the affected women to fulfill gender role expectations fostered stigma. Emotional and sexual violence increased their vulnerability, highlighting the lack of life options outside marriage and silencing most of them into accepting the violence. Initiatives need to be developed to address misperceptions regarding the causes of such disabilities and, in the long-term, create economic opportunities for reducing the dependence of women on marriage and men and transform the society to overcome rigid gender norms. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11312 J HEALTH POPUL NUTR 2012 Jun;30(2):181-192